A Psychometric Investigation of the Hate-Motivated Behavior Checklist - Cramer, Robert J. (Journal of interpersonal violence, 2023)
Hate-motivated behavior (HMB) comprises a continuum ranging from microaggressions to criminal acts. The measurement of HMB is limited primarily to one or two minoritized groups in any given instrument. Current HMB research also lacks a way to assess the full range of acts and motivations for bias-based behavior. The present study fills gaps in HMB measurement by conducting a psychometric study of the Hate-Motivated Behavior Checklist (HMBC). The HMBC is a self-report instrument of HMB perpetration; the instrument also has sections capturing victim target group (e.g. race, sexual orientation, disability) and perpetrator motivation for HMB commission (e.g., perceived threat, impulsivity). We conducted an online cross-sectional survey of community-dwelling adults and college students (N = 463). Measures assessed demographic information, HMB, and social-political characteristics. Confirmatory factor analysis, item response theory analyses, between-groups analyses (e.g., Analysis of Variance), and descriptive statistics were used to examine HMBC properties. Primary findings included (1) poor model fit of the HMBC behaviors score; (2) good model fit with high reliability for an HMBC behaviors score adapted to binary (no/yes) scoring; (3) men reported meaningfully higher HMB scores compared to women; (4) the most common target classification for HMB was based on political affiliation; and (5) perceived intrusion was the most cited reason for committing HMB. Our findings are an important step in refining the HMBC. The instrument represents a potentially useful tool for HMB research, surveillance, and intervention evaluation. Future directions in HMBC research include application to extremist and criminal samples, replication and extension of the binary scoring to include cut-score derivation, and validation against behavioral outcomes.